The standardization of the Polish version of the Alberta Infant Motor Scale - Małgorzata Eliks; Sowińska Anna; Steinborn Barbara; Ewa Gajewska (BMC, 2023)
Abstract Background The Alberta Infant Motor Scale (AIMS) is a standardized tool for assessing gross motor development from birth through independent walking (0-18 months). The AIMS was developed, validated and standardized in the Canadian population. Results of previous studies on the standardization of the AIMS have discerned differences in some samples in comparison with Canadian norms. This study aimed to establish reference values of the AIMS for the Polish population and compare them to Canadian norms. Methods The research involved 431 infants (219 girls, 212 boys, aged 0-<19 months), divided into nineteen age groups. The translated into Polish and validated version of the AIMS was used. The mean AIMS total scores and percentiles for every age group were calculated and compared with the Canadian reference values. Raw total AIMS scores were converted to 5th, 10th, 25th, 50th, 75th, and 90th percentiles. A one sample t-test was used to compare the AIMS total scores between Polish and Canadian infants (p-value < 0.05). A binomial test was performed to compare percentiles (p-value < 0.05). Results The mean AIMS total scores in the Polish population were significantly lower in the seven age groups: 0-<1, 1-<2, 4-<5, 5-<6, 6-<7, 13-<14, and 15-<16 months of age (with small to large effect size). A few significant differences were found in the comparison of percentile ranks, mostly in the 75th percentile. Conclusion Our study provides the norms for the Polish AIMS version. According to differences in the mean AIMS total scores and percentiles, the original Canadian reference values are not congruent for Polish infants. Trial registration ClinicalTrials.gov ID NCT05264064. URL https://clinicaltrials.gov/ct2/show/NCT05264064 . Date of registration: 03/03/2022.